Turismo e desenvolvimento de áreas de baixa densidade: As Aldeias Históricas de Portugal de Trancoso e Marialva - Reis, Paula (2013)
The changes undergone in the past years in rural communities make us reconsider the development models applied in these communities, especially what concerns to the use of local resources and promotion of economic activities – tourism.The present paper is the result of an exploratory and analytical research (in 2010) that intended to contribute to clarify the role of tourism in the development of a territory eminently rural, the Historic Villages of Portugal, Trancoso and Marialva. The study also helps to analyze and understand the contribution of the implementation of tours in the local development process.